Accumulation of Magnetic Nanoparticles Employing High Intensity Focused Ultrasound for Drug Targeting Applications - Fink, Michael; George, Benedikt; Rupitsch, Stefan; Ermert, Helmut (Proceedings of the Ultrasonics Symposium (IUS), 2018)

Characterisation of Sonosensitive Nano-Sized Formulations - Hiltl, Pia-Theresa; George, Benedikt; Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Lee, Geoffrey (3rd European Conference on Pharmaceutics, 2019)

Determination of the Cavitation Pressure Threshold in Focused Ultrasound Wave Fields applied to Sonosensitive, Biocompatible Nanoparticles for Drug Delivery Applications - George, Benedikt; Lehner, Markus; Fink, Michael; Rupitsch, Stefan; Hiltl, Pia-Theresa; Savsek, Ula; Lee, Geoffrey; Ermert, Helmut (Current Directions in Biomedical Engineering 2020, 2020)

Guiding and Accumulation of Magnetic Nanoparticles Employing High Intensity Focused Ultrasound for Drug Targeting Applications - George, Benedikt; Fink, Michael; Ermert, Helmut; Rupitsch, Stefan; Lyer, Stefan; Alexiou, Christoph (Current Directions in Biomedical Engineering, 2019)
Magnetic Drug Targeting (MDT) is a cancer treatment technique that enables a local chemotherapy. In MDT, chemotherapeutic drugs are bound to magnetic nanoparticles and are accumulated in the tumor area by means of an external magnetic field. Unfortunately, a single magnet can only generate a pulling magnetic force. However, in some applications a pushing force on the nanoparticles could be advantageous. One way to realize pushing forces is to exploit the acoustic radiation force based on the nonlinearity of sound propagation in fluid media generated by a high intensity focused ultrasonic transducer. In this context, we built a test setup was built to investigate the utility of High Intensity Focused Ultrasound (HIFU) to generate a pushing force on the magnetic nanoparticles. The results show that the acoustic radiation force can be employed for particle guidance to achieve concentration differences similar to those obtained by using an electromagnet.
CRIS-Team Scopus Importer:2022-06-27
Keywords: acoustic radiation force; drug targeting; nanoparticles; Ultrasound

Guiding and Accumulation of Magnetic Nanoparticles Employing High Intensity Focused Ultrasound for Drug Targeting Applications - George, Benedikt; Fink, Michael; Rupitsch, Stefan; Ermert, Helmut; Alexiou, Christoph; Lyer, Stefan (Current Directions in Biomedical Engineering 2019, 2019)

Investigation of Inertial Cavitation Stimulation by Focused Ultrasound on Sonosensitive Nanoparticles for Drug Delivery Applications - George, Benedikt; Fink, Michael; Rupitsch, Stefan; Hiltl, Pia-Theresa; Lee, Geoffrey; Ermert, Helmut (Proceedings IEEE IUS 2019, 2019)

Investigation of the Inertial Cavitation Activity of Sonosensitive and Biocompatible Nanoparticles for Drug Delivery Applications Employing High Intensity Focused Ultrasound - George, Benedikt; Rupitsch, Stefan; Fink, Michael; Ermert, Helmut; Hiltl, Pia-Theresa; Lee, Geoffrey (Current Directions in Biomedical Engineering 2019, 2019)

Measurement of the Cavitation Activity of Sonosensitive Nanoparticles used for Local Chemotherapy - George, Benedikt; Fink, Michael; Plock, Maren; Hiltl, Pia-Theresa; Ermert, Helmut; Lee, Geoffrey; Rupitsch, Stefan (6. Tagung Innovation Messtechnik, 2019)
Keywords: Messtechnik; Sensoren; Messelektronik

Ultrasound-based Detection of Objects in Grain Fields - Tröndle, Florian; George, Benedikt; Hubert, Florian; Rupitsch, Stefan J. (22. GMA/ITG-Fachtagung Sensoren und Messsysteme 2024, 2024)
Foreign objects in a crop, such as stones, can cause serious damages if they collide with a grain harvester. Machine damages result in downtimes during the tightly scheduled harvesting phase and lead to additional costs. Currently, there are no technical systems that warn an operator in the case of a collision with foreign objects during harvesting. Therefore, this contribution examines ultrasound-based methods for stone detection. Since ultrasonic sensors are very robust and reliable, these transducers are very common in the agricultural sector. The propagation of acoustic waves within a grain field was examined using a realistic replication. The evaluation criteria during the experiments were the attenuation of the acoustic signal by the crop, the influence of the soil and the arrangement of the ultrasonic sensors. We used mono-frequency, sinusoidal burst sequences with a frequency of 50 kHz and a duty cycle of 0.01 % as acoustic stimulation signals. A synthetic aperture focusing technique was applied to improve the lateral resolution. A vertical alignment of the ultrasonic transducers produced the best possible object resolution.<br